Micromethod for plasma cefuroxime quantification through high performance liquid chromatography: application to the prophylaxy of patients submitted to cardiac surgery (Revista Brasileira de Ciências Farmacêuticas, 2003)
An improved, simple, selective and sensitive micromethod based on HPLC-UV is described to determine cefuroxime plasma levels, a second generation cephalosporin. Once changes on pharmacokinetics of drugs in patients submitted to heart surgery with cardiopulmonary bypass and hypothermia (CPB-H) were reported previously, the objective of the present study was to investigate cefuroxime plasma levels for antimicrobial prophylaxis of infections in those patients after surgery using HPLC-UV. Only 200 µL of plasma were required, and cefuroxime was determined by a chromatographic method using reversed phase system, after a simple clean up of plasma samples. Peaks monitored at 280 nm were eluted isocratically at 12.5 min (cefuroxime) and at 4.0 min (vancomicyn, internal standard,) from a 4 µm, NovaPak column (150 x 3.9 mm) using a binary mobile phase at flow rate 0.8 mL/min, consisting of 0.375 M acetate buffer, pH 5,0 and acetonitrile, 96:4 (v/v). The method validated with basis of parameters evaluated for the confidence limits of cefuroxime measurements in spiked blank plasma, presents 0.1 µg/mL sensitivity, 0.2 - 200 µg/mL linearity, (r² 0.998), systematic error of 98.2% and 96.9% (intra- and interday accuracy), intra- and interday precision (CV %: 3.2 % and 4.2 %). A good stability and high percentage of recovery (99.2%) were obtained. Patients received cefuroxime 6 g i.v. bolus (1,5 g, 4 times in 24 hours), showed in the first postoperative day plasma levels of 108.0 µg/mL (zero), 32.8 µg/mL (3rd h), 9.9 µg/mL (6th h), 3.4 µg/mL (9th h) and 0.8 µg/mL (12th h), after the last dose.